EXPLORING SELF-DETERMINATION AND EDUCATIONAL IDEALS IN PURSUIT OF HAPPINESS BY GABRIEL MUCCINO - Yuanita, Tanty; Said, Mashadi; Saragih, Gustaman (Universitas Indraprasta PGRI, 2024)
The aim of this research is to analyze self-determination and educational ideals in